TRANSFORMATION OF THE SYSTEM OF PROVISION OF SOCIAL SERVICES IN UKRAINE IN THE CONTEXT OF CHANGES IN THE PARADIGM OF SOCIAL SUPPORT: INTERNATIONAL STANDARDS AND FOREIGN PRACTICES - Kalashnyk, Nadiia; Olefirenko, Olga (Public Management and Policy, 2026)
The article analyzes international standards and foreign experience in organizing social services in the context of modern socio-economic transformations, digitalization and the growth of the role of territorial communities in the system of social protection of the population. It is revealed that the modern development of the social services system requires a combination of national legal regulation with international practices of supporting people in difficult life circumstances. It is established that international approaches are based on the principles of human-centricity, targeting, continuity, professionalism, intersectoral interaction and orientation on results for the recipient of services. The approaches of the European Union as a supranational institution, Great Britain, Germany, Poland, Scandinavian countries and Canada to the organization of social support, needs assessment, standardization, quality monitoring, participation of non-state providers and involvement of service recipients in assessing the effectiveness of assistance are analyzed. It is determined that the European model of digitalization of social services is not based on a single regulatory act, but is formed through a system of interconnected strategies, regulations and programs aimed at ensuring accessibility, integration, digital compatibility and human-centricity of social services. Particular attention is paid to the role of digital tools, interagency integration, ethical principles of using artificial intelligence and development of digital infrastructure in the field of social protection. It is substantiated that for Ukraine, in the conditions of European integration, digitalization, decentralization and martial law, the key challenge is the formation of its own adaptive model of social service provision. International standards should be considered as a framework guideline that requires adaptation to the financial capacity of the state and territorial communities, security challenges and the specifics of the social needs of the population. The feasibility of developing a multi-level system of social services with differentiation by population groups and levels of assistance, expanding the participation of the non-state sector, improving the professional training of personnel and introducing digital management and case management mechanisms has been proven. Of particular importance is the search for ways to optimize costs through the digitalization of procedures, the integration of information systems and the development of remote support services. Prospects for further research are related to the development of models for assessing the effectiveness of social services in communities, the analysis of digital case management and the definition of optimal formats for intersectoral interaction.